2017
DOI: 10.1177/1098612x17693490
|View full text |Cite
|
Sign up to set email alerts
|

Haematology and coagulation profiles in cats with congenital portosystemic shunts

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms Results: Fourty-two cats were included. Thirty-six cats (87.5%) had an extrahepatic CPSS and six (14.3%) had an intrahepatic CPSS. Pre-operatively, mean cell volume (MCV) and mean cell haemoglobin (MCH) were below the reference interval in 32 (76.2%) and 31 (73.8%) cats respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…However, thrombosis was not described in any cat, and hence, this study was judged to oppose the PECO question 135 . Two other studies (LOE 5, fair) identified hemostatic abnormalities in cats with cPSS, but neither described thrombosis 136,137 . These studies were considered neutral to the PECO question.…”
Section: Peco Question: Congenital Portosystemic Shunts (Cpss) (Cats)mentioning
confidence: 95%
See 1 more Smart Citation
“…However, thrombosis was not described in any cat, and hence, this study was judged to oppose the PECO question 135 . Two other studies (LOE 5, fair) identified hemostatic abnormalities in cats with cPSS, but neither described thrombosis 136,137 . These studies were considered neutral to the PECO question.…”
Section: Peco Question: Congenital Portosystemic Shunts (Cpss) (Cats)mentioning
confidence: 95%
“…135 Two other studies (LOE 5, fair) identified hemostatic abnormalities in cats with cPSS, but neither described thrombosis. 136,137 These studies were considered neutral to the PECO question.…”
Section: Evidence Summarymentioning
confidence: 99%
“…Hematological and immunological manifestations are anecdotally reported in CPSS patients and are linked to the reticuloendothelial role of the liver for the latter [ 3 ]. Animal studies have demonstrated changes in levels of clotting factors and anticoagulants in the presence of CPSS [ 81 ]. In humans, cases are scarce, and include one patient with coagulation abnormalities on pre-operative work-up [ 33 ], a single report of vaginal bleeding linked to a meso-iliac fistula [ 56 ] and a retrospective report of 19 cases with mild coagulopathy [ 82 ].…”
Section: Other Symptoms and Signs Of Cpssmentioning
confidence: 99%
“…6,7 These studies show that platelet counts are typically normal, but many cats (40–82%) have either an abnormal PT or aPTT. 6,810 In the majority of these cats, PT prolongation is accompanied by low factor VII activity and reflects a vitamin K1-responsive coagulopathy. 6,7 A limited number of studies have looked beyond conventional coagulation testing and have shown that additional hemostatic testing abnormalities might be associated with both bleeding (decreased fibrinogen or factor XIII activity) or thrombotic tendencies (increased fibrinogen or D-dimers; decreased protein C or antithrombin activity) in cats with various types of hepatic disease.…”
Section: Introductionmentioning
confidence: 99%